Assessment of Early Microvascular Changes in the Eye and Ear in Patients with Metabolic Syndrome: A Cross-Sectional Study - Rehan Moinuddin Shaikh, Allah Bux Mushtaq, Ahsan Qureshi, Jamshad Ahmed, Junaid Hussain, Anwar Ul Haq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Metabolic syndrome (MetS) is a cluster of metabolic abnormalities, including central obesity, insulin resistance, hypertension, and dyslipidemia. These factors contribute to systemic microvascular dysfunction, which may manifest early in highly vascularized organs such as the eye and ear. Early detection of subclinical microangiopathy could serve as a biomarker for impending systemic vascular complications. Objective: To assess early microvascular changes in the retina and cochlea in patients with metabolic syndrome using non-invasive ophthalmological and audiological methods. Methods: A cross-sectional study was conducted from January 2022 to May 2023 at Mughal Eye Hospital, Lahore, and Pir Abdul Qadir Shah Jilani Institute of Medical Sciences, Gambat. A total of 100 participants were enrolled, including 70 patients with MetS (per IDF criteria) and 30 healthy controls. Retinal vessel diameters were assessed through fundus photography, and microvascular perfusion was evaluated using optical coherence tomography angiography (OCT-A). Cochlear function was examined using pure tone audiometry (PTA) and distortion product otoacoustic emissions (DPOAEs). Biochemical parameters including fasting glucose, lipid profile, and hsCRP were recorded. Results: Patients with MetS showed significantly narrower retinal arteriolar diameters (CRAE: 134.6 ± 10.5 µm) and wider venular diameters (CRVE: 231.1 ± 15.3 µm) compared to controls (p < 0.001). OCT-A revealed reduced capillary density and enlarged foveal avascular zone (FAZ) (p = 0.008). High-frequency sensorineural hearing loss was present in 45.7% of MetS patients, with 52.9% showing absent or diminished DPOAEs. Positive correlations were found between triglyceride levels and both retinal and cochlear changes (p < 0.01). Conclusion: Metabolic syndrome is associated with early subclinical microvascular changes in the eye and ear. Fundus imaging, OCT-A, and basic audiological assessments can serve as non-invasive, cost-effective tools for early detection and monitoring of microvascular impairment in MetS. These findings underscore the importance of multidisciplinary screening approaches in managing cardiometabolic risk. Keywords: Metabolic syndrome, retinal microvasculature, cochlear dysfunction, OCT-A, otoacoustic emissions, microangiopathy.